Workshop on Palm Oil Technical Promotion and Market Development : proceedings - Workshop on Palm Oil Technical Promotion and Market Development (1982 : Kuala Lumpur); PORIM (Kuala Lumpur : Institut Penyelidikan Minyak Kelapa Sawit Malaysia, 1983)
36